An Evaluation on the Effectiveness of Work Health and Safety Management System A Case Study of ‘Universitas Gadjah Mada’ Hospital Yogyakarta - Vira Dwi Martha (ABIS: Accounting and Business Information Systems Journal, 2016)
This research aims to evaluate the adoption of occupational health and safety management system at ’Universitas Gadjah Mada’ Hospital, to assess the effectiveness of work health and safety management system at ’Universitas Gadjah Mada’ Hospital based on the Committee of Sponsoring Organization of the Treadway Commission (COSO), the Government Regulation No. 50, 2012, the Indonesian Minister of Health’s Decree No. 432/MENKES/SK/IV/2007, and ’Universitas Gadjah Mada’ Hospital’s President Director’s Decision No. 127/SK/RS-UGM/VII/2015; and to offer an input for a more effective implementation.This research uses a qualitative method, the samples were selected using a purposive sampling technique, which means that the samples chosen are correlated with work health and safety risks, 10 resource persons were selected to represent 7 work units under the condition that one person is chosen from each unit, except from the cleaning service unit, where four persons were chosen due to differences of workplace risks. The data collection was performed using in-depth interviews under the guidance of Internal Control Questionnaires (ICQ); observational survey; document inspection; confirmation and documentation. The data collected were analyzed and then conclusions were drawn to answer the research questions. Results of this research are the design of work health and safety management system at ’Universitas Gadjah Mada’ Hospital is considered sufficient with a note, because it complies with all the Committee of Sponsoring Organization of the Treadway Commission (COSO) criteria, but it is yet to undergo an internal audit, the implementation of work health and safety management system at ’Universitas Gadjah Mada’ Hospital is quite effective because all of the Committee of Sponsoring Organization of the Treadway Commission (COSO) criteria have been implemented, with a note that although the decision letter for health examination program has been issued, it hasn’t been executed, and there are still some obsolete data.